Exploring the Link Between C‐Reactive Protein Change and Stroke Risk: Insights From a Prospective Cohort Study and Genetic Evidence - Ling, Yitong; Yuan, Shiqi; Cheng, Hongtao; Tan, Shanyuan; Huang, Xiaxuan; Tang, Yonglan; Bai, Zihong; Li, Rui; Li, Li; Li, Shuna; Huang, Liying; Xu, Anding; et al. (Journal of the American Heart Association, 2025)
Previous research on how changes in CRP (C-reactive protein) levels predict stroke risk is limited. This study aimed to examine the association between CRP change and the risk of stroke and its subtypes. Based on the UK Biobank data, we investigated the association between CRP change and the risk of stroke and its subtypes with Cox proportional hazards regression analysis. We further performed genetic analyses including genetic correlation, pairwise genome-wide association study, and polygenic risk score. Our study involved 14 754 participants with a median follow-up time of 10.4 years. After categorizing participants by CRP percentage change and making adjustments for potential confounders, it was observed that those with an elevated percentage of CRP change had a higher risk of any stroke (hazard ratio [HR], 1.44 [95% CI, 1.12-1.85]) and ischemic stroke (HR, 1.65 [95% CI, 1.24-2.18]). After categorization by CRP change types and adjustment for confounders, the group that became high level had a higher any-stroke risk (HR, 1.45 [95% CI, 1.04-2.02]), with the group that remained at a high level facing the greatest risk (HR, 1.74 [95% CI, 1.30-2.33]). Similar trends were observed for ischemic stroke. The group that remained at a high level also had a heightened hemorrhagic stroke risk (HR, 1.91 [95% CI, 1.07-3.44]). Genetic analysis showed a significant genetic correlation between CRP and stroke (r , 0.257; r _ =2.39E-07). Pairwise genome-wide association study analysis identified 5 shared genomic regions between CRP and stroke. Polygenic risk score analysis showed that participants with high stroke polygenic risk score and elevated or remaining high CRP levels have the highest risk of stroke. Both any stroke and ischemic stroke are related to elevated and remaining high CRP levels, while hemorrhagic stroke is only related to remaining high CRP levels.